Enhanced photocatalytic degradation of Rhodamine B, antibacterial and antioxidant activities of green synthesised ZnO/N doped carbon quantum dot nanocomposites. (16th November 2021) - Tadesse, Aschalew; Hagos, Mebrahtu; Belachew, Neway; Murthy, H. C. Ananda; Basavaiah, K.
Abstract : In order to explore an alternative photocatalyst for environmental remediation, we report a two-step process for the synthesis of zinc oxide/nitrogen doped carbon quantum dot nanocomposites (ZnO@NCQD NCs). Abstract : In order to explore an alternative photocatalyst for environmental remediation, we report a two-step process for the synthesis of zinc oxide/nitrogen doped carbon quantum dot nanocomposites (ZnO@NCQD NCs). In the first step, graphitic amorphous nitrogen doped carbon quantum dots (NCQDs) were synthesised using sesame oil and urea as precursors via a hydrothermal method. A facile one pot coprecipitation method was used to synthesise white-brown ZnO@NCQD NCs by mixing zinc acetate and NCQD solution. The ZnO@NCQD NCs were characterized by advanced techniques to confirm their morphological, structural and optical features. TEM (transmission electron microscopy) analysis corroborated the formation of well-defined uniformly distributed quasi-spherical NCQDs with an average particle size of about 5.5 nm. Spherical shaped nanostructures of ZnO@NCQD NCs were observed from the SEM (scanning electron microscopy) micrographs. The XRD (X-ray diffraction) result revealed the hexagonal wurtzite polycrystalline structure of ZnO@NCQD NCs. A decrease in the band gap energy of ZnO@NCQD NCs (3.01 eV) was observed due to the insertion of NCQDs into the structure of zinc oxide nanoparticles (ZnO NPs). The FTIR spectra confirmed the presence of hydroxyl and amine functional groups on the surface of NCQDs which are expected to have played a significant role in the process of functionalization and synthesis of ZnO@NCQD NCs. A photocatalytic degradation efficiency of 92% was recorded for Rhodamine B (Rh-B) dye by ZnO@NCQD NCs as a consequence of the reduced band gap. In addition, ZnO@NCQD NCs exhibited highly impressive antibacterial and antioxidant properties. Thus ZnO@NCQD NCs can serve as better materials for environmental as well as biomedical applications.